IVF Children Acquiring Emirati Citizenship by the Nationality of a Parent (Jus Sanguinis) - Enizi, Ziad Al; Mahameed, Waleed Fouad (Bangladesh Journal of Medical Science, 2023)
Objective. The technology of in vitro fertilization (IVF) opened a new era in the treatment of infertility but at the same time it created new challenges for civil and international private law. This concerns the issues of determining and/or acquiring child citizenship and legal conflicts associated with this. Materials and methods. This study examines the aspects of obtaining UAE citizenship through the study of the UAE Citizenship Law and the principle of jus sanguinis (right of blood) when citizenship is acquired by a parent’s nationality. The research aims to identify whether the current legislative regulation of the UAE meets the current challenges in the field of family relations against the backdrop of new medical advances in IVF. The paper considers the aspects of the UAE legal regulation in the scope of family law relationships. The above issues were considered from the critical evaluation prospects taking into account the potential ways for their improvement. Results and Discussion. The problems associated with determining the citizenship for those born as a result of IVF are the subject of discussion, while, as practice shows, the law often does not keep pace with the development of reproductive technologies. Based on the analysis of legal regulation and practice, the study summarizes the grounds for obtaining UAE citizenship by children conceived through IVF and refusals to obtain it. Conclusion. The paper recommends mitigating the requirement of proof of paternity as a condition to grant the nationality to an IVF child, especially in the case of purely medical errors in which father has no responsibility. Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 676-686